2022
DOI: 10.47723/kcmj.v18i3.813
|View full text |Cite
|
Sign up to set email alerts
|

Practice & Opinion of Doctors in Hospitals toward Referral System in Iraq

Abstract: Background: Primary Health care (PHC) is unanimous to be the cornerstone of a person-centered health system. While the adoption of a well-function, two-way, and organized referral system is the mainstay in the development of an efficient healthcare delivery system.   Objective: To Assess the practice & opinion of doctors in the hospitals toward the referral system.  to determine the doctors in the hospital's commitment to referral system instructions and guidelines. Subjects and Methods: A cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A referral system is essential for primary care as it serves as a means to coordinate clinical care between different facilities, streamline the continuity of patient care, and improve the quality of care [ 33 ]. Eighty-five percent of PHCs in Iraq have a referral system, yet 64% of these centers reported a lack of a feedback mechanism about these referrals [ 34 ]. A study that explored the effect of implementing a referral system in the governorate of Wasit showed that after three months of applying the referral system, the number of visits to the local hospital was reduced by one-third compared to the period prior, and the number of PHC visits doubled for the same period [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…A referral system is essential for primary care as it serves as a means to coordinate clinical care between different facilities, streamline the continuity of patient care, and improve the quality of care [ 33 ]. Eighty-five percent of PHCs in Iraq have a referral system, yet 64% of these centers reported a lack of a feedback mechanism about these referrals [ 34 ]. A study that explored the effect of implementing a referral system in the governorate of Wasit showed that after three months of applying the referral system, the number of visits to the local hospital was reduced by one-third compared to the period prior, and the number of PHC visits doubled for the same period [ 35 ].…”
Section: Resultsmentioning
confidence: 99%